Effect of chicken gonadotropin-releasing hormone (cGnRH-II) on plasma steroid hormone, maturation and ovulation in African catfish, Clarias gariepinus (Burchell) - Taufek, Norhidayah; Harmin, Sharr Azni; Christianus, Annie (Academic Journals, 2009)
Nowadays, many studies on the effects of native GnRHs and various agonists have been evaluated on the spawning of African catfish, Clarias gariepinus. For the current study, three experiments have been conducted to determine the effectiveness of chicken gonadotropin-releasing hormone II (cGnRH-II) in stimulation of maturation and ovulation of African catfish. The first experiment concerned the graded dosage treatment; the second experiment was designed specifically to determine the response of dopamine inhibitor to accelerate the maturation process. Finally the third experiment was carried out to compare the effectiveness of cGnRH-II against leutinising hormone releasing-hormone analogue (LHRHa) and salmon gonadotropin-releasing hormone analogue (sGnRHa) in inducing maturation and ovulation. Plasma steroid levels (17ß-estradiol (E2) and testosterone) were determined and germinal vesicle (GV) was observed prior to hormone administration at (0), 6, 12 and 24 h post injection. From the first experiment, cGnRH-II 200 μg/kg was found to be effective to induce ovulation in African catfish. 100% ovulation was also observed for the fish treated with cGnRH-II 200 μg/kg with the combination of pimozide based on the second experiment. Finally in the third experiment, sGnRHa was proven to be more efficient compared to cGnRH-II, only 20 μg/kg was administered intramuscularly in single injection. For the group that showed ovulation, that is cGnRH 200 μg/kg alone and with the combination of pimozide and also sGnRHa, plasma level of E2 and T increased significantly with the association of germinal vesicle migration and ultimately ovulation. The concentration reached the peaked after 12 h, then decreased dramatically at 24 h post treatment. In contrast to the non-ovulated group that is cGnRH-II 2 and 20 μg/kg, the plasma level showed small increased after the injection and throughout the experiment. The present study indicates that administration of cGnRH-II is effective for sexual maturation and ovulation in African catfish.